Interspecies Isobaric Labeling-Based Quantitative Proteomics Reveals Protein Changes in the Ovary of Aedes aegypti Coinfected With ZIKV and Wolbachia - Ramos, Luís Felipe Costa; Martins, Michele; Murillo, Jimmy Rodriguez; Domont, Gilberto Barbosa; de Oliveira, Danielle Maria Perpétua; Nogueira, Fábio César Sousa; Maciel-de-Freitas, Rafael; Junqueira, Magno (Frontiers in Cellular and Infection Microbiology, 2022)
Zika is a vector-borne disease caused by an arbovirus (ZIKV) and overwhelmingly transmitted by Ae. aegypti. This disease is linked to adverse fetal outcomes, mostly microcephaly in newborns, and other clinical aspects such as acute febrile illness and neurologic complications, for example, Guillain-Barré syndrome. One of the actual most promising strategies to mitigate arbovirus transmission involves releasing Ae. aegypti mosquitoes carrying the maternally inherited endosymbiont bacteria Wolbachia pipientis. The presence of Wolbachia is associated with a reduced susceptibility to arboviruses and a fitness cost in mosquito life-history traits as fecundity and fertility. However, the mechanisms by which Wolbachia influences metabolic pathways leading to differences in egg production remains poorly known. To investigate the impact of co-infections on the reproductive tract of the mosquito, we applied an isobaric labeling-based quantitative proteomic strategy to investigate the influence of Wolbachia wMel and ZIKV infection in Ae. aegypti ovaries. To the best of our knowledge, this is the most complete proteome of Ae. aegypti ovaries reported so far, with a total of 3,913 proteins identified, also,were able to quantify a total of 1,044 Wolbachia proteins in complex sample tissue of Ae. aegypti ovary.. Furthermore, we discuss proteins and pathways altered in Ae. aegypti during ZIKV infections, Wolbachia infections, co-infection Wolbachia/ZIKV, and compared with no infection, focusing on immune and reproductive aspects of Ae. aegypti. The modified aspects were mostly related to the immune priming enhancement by Wolbachia presence and the modulation of the Juvenile Hormone pathway caused by both microorganisms infection.